1999
DOI: 10.1029/1999gl900226
|View full text |Cite
|
Sign up to set email alerts
|

Size distributions of NLC particles as determined from 3‐color observations of NLC by ground‐based lidar

Abstract: Abstract. From June to August 1998 the ALOMAR Rayleigh/Mie/ Raman lidar, located at 69øN and 16øE in Northem Norway, repeatedly observed noctilucent clouds (NLCs) overhead the lidar. Due to a recent upgrade in detector technology, the lidar was able to obtain 151 hours of NLC observations, simultaneously at 355, 532, and 1064 nm. For the 11 strongest NLC events, we have calculated size distributions for the NLC particles from the b•kscatter ratios measured at the 3 wavelengths and using the assumptions of sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
190
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(212 citation statements)
references
References 13 publications
21
190
1
Order By: Relevance
“…The ALOMAR lidars (von Zahn et al, 1995) observed strong NLC from 82.1 to 84.1 km at the launch time. This NLC layer varied considerably in height with time and extended down to ∼81 km only ∼10 min before launch and well below 81 km ∼45 min after launch.…”
Section: The Dust Experiments and The Launch Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ALOMAR lidars (von Zahn et al, 1995) observed strong NLC from 82.1 to 84.1 km at the launch time. This NLC layer varied considerably in height with time and extended down to ∼81 km only ∼10 min before launch and well below 81 km ∼45 min after launch.…”
Section: The Dust Experiments and The Launch Conditionsmentioning
confidence: 99%
“…12 with Z d =−1. For layer 1, which most likely consists of fairly large NLC dust particles of radius r d ≈50±20 nm (von Cossart et al, 1999;Eremenko et al, 2005), the real Z d should be higher than −1, a likely charge range could be Z d =−2 to −4. This shows that for this NLC/PMSE layer, the production factor η s (max) may well be from 50 to 100.…”
Section: Secondary Charge Production In the Nlc/pmse And Pmse Layermentioning
confidence: 99%
See 2 more Smart Citations
“…The first observation of simultaneous and common-volume observations of NLC measured by lidar and PMSE were published by Nussbaumer et al (1996), who presented four cases and identified tightly and loosely coupled layers. This dataset, obtained at ALOMAR, was extended by von Zahn and Bremer (1999) presenting 22 cases and defining three types of layers, namely PMSE and NLC in a common volume, which accounted for 63% of all cases, layers with temporal differences (16%) and spatial differences (21%). PMSE and NLC have also been observed at other locations, among them Spitsbergen , Poker Flat, Alaska (Taylor et al, 2009) and Antarctica (Klekociuk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%